An application of the direct strength method to the design of castellated beams subject to flexure. (15th September 2021) - Weidlich, Christovam M.; Sotelino, Elisa D.; Cardoso, Daniel C.T.
Highlights: A comprehensive numerical study of castellated beams is proposed. Eigenvalue and fully nonlinear FEA with geometric imperfections are conducted. An approach based on the Direct Strength Method is proposed and equations derived. The method is then compared with current standards procedures showing good results. Abstract: The aim of this research is to investigate the instability of castellated beams and the interaction between lateral-torsional and compression tee local buckling modes. Firstly, a comprehensive study of 197 simply supported Litzka castellated beams under pure bending is carried out. The study involves eigenvalue and fully nonlinear finite element analyses, e.g. including both material nonlinearity and geometric imperfections. After computing the critical moments associated to local and global modes and the ultimate moments, an approach based on the Direct Strength Method is proposed using regression techniques to derive strength prediction equations. The developed method is then compared with current standards procedures. The results show that the proposed equation predicts better strength values in all cases, especially those in which local and/or interaction failure modes dominate the behavior of the beam. The results also show that some of the procedures suggested in standards and guides for the design of castellated beams under flexure, either underestimate or overestimate the failure moment when considering the interaction between global buckling mode and plastification.